Protists Within Corals: The Hidden Diversity - Clerissi, Camille; Brunet, Sébastien; Vidal-Dupiol, Jeremie; Adjeroud, Mehdi; Lepage, Pierre; Guillou, Laure; Escoubas, Jean-Michel; Toulza, Eve (Frontiers in Microbiology, 2018)
Previous observations suggested that microbial communities contribute to coral health and the ecological resilience of coral reefs. However, most studies of coral microbiology focused on prokaryotes and the endosymbiotic algae Symbiodinium. In contrast, knowledge concerning diversity of other protists is still lacking, possibly due to methodological constraints. As most eukaryotic DNA in coral samples was derived from hosts, protist diversity was missed in metagenome analyses. To tackle this issue, we designed blocking primers for Scleractinia sequences amplified with two primer sets that targeted variable loops of the 18S rRNA gene (18SV1V2 and 18SV4). These blocking primers were used on environmental colonies of Pocillopora damicornis sensu lato from two regions with contrasting thermal regimes (Djibouti and New Caledonia). In addition to Symbiodinium clades A/C/D, Licnophora and unidentified coccidia genera were found in many samples. In particular, coccidian sequences formed a robust monophyletic clade with other protists identified in Agaricia, Favia, Montastraea, Mycetophyllia, Porites, and Siderastrea coral colonies. Moreover, Licnophora and coccidians had different distributions between the two geographic regions. A similar pattern was observed between Symbiodinium clades C and A/D. Although we were unable to identify factors responsible for this pattern, nor were we able to confirm that these taxa were closely associated with corals, we believe that these primer sets and the associated blocking primers offer new possibilities to describe the hidden diversity of protists within different coral species.